1994
DOI: 10.1056/nejm199405193302003
|View full text |Cite
|
Sign up to set email alerts
|

Imipramine in Patients with Chest Pain Despite Normal Coronary Angiograms

Abstract: Imipramine improved the symptoms of patients with chest pain and normal coronary angiograms, possibly through a visceral analgesic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
185
1
8

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(198 citation statements)
references
References 49 publications
4
185
1
8
Order By: Relevance
“…20 However, our study showed that, although a significant decrease in pain intensity was recorded, there was no change in the motility pattern at the end of the study. This is in contrast with earlier studies, in which the motility pattern changed with time, 31 but in agreement with earlier studies of trazodone 24 and imipramine, 32 where pain relief was accomplished without any effect on motility. These results suggest that the role of the contractile abnormality in the pathophysiology of non-cardiac chest pain in nutcracker oesophagus is small, if any.…”
supporting
confidence: 88%
“…20 However, our study showed that, although a significant decrease in pain intensity was recorded, there was no change in the motility pattern at the end of the study. This is in contrast with earlier studies, in which the motility pattern changed with time, 31 but in agreement with earlier studies of trazodone 24 and imipramine, 32 where pain relief was accomplished without any effect on motility. These results suggest that the role of the contractile abnormality in the pathophysiology of non-cardiac chest pain in nutcracker oesophagus is small, if any.…”
supporting
confidence: 88%
“…931 Imipramine 50 mg daily has been successful in some chronic pain syndromes, including syndrome X, reducing the frequency of chest pain by 50%. 932 Transcutaneous electrical nerve stimulation and spinal cord stimulation can offer good pain control. 933,934 Estrogen in postmenopausal women with angina and normal coronary arteriograms has been shown to reverse the acetylcholine-induced coronary arterial vasoconstriction, presumably by improving endothelium-dependent coronary vasomotion, 935 and to reduce the frequency of chest pain episodes by 50%.…”
Section: Treatmentmentioning
confidence: 99%
“…Digno de nota também é o fato de que 7 (39%) desses 18 pacientes estavam sendo tratados com ADTs em doses máximas não maiores que 75 mg/dia. Embora eficaz para o tratamento da dor torácica 8,9 , essa dose não é suficiente para o tratamento may partially ameliorate depressive symptoms, making the appropriate diagnosis and treatment of major depression even more difficult, consequently contributing to the persistence of pain and other complains. Considering the wide alternatives to effectively treat depression, a focus on detection and treatment of major depression in patients with chest pain is warranted by clinicians and researchers.…”
Section: Discussionunclassified